Age of First Infection of Pulmonary Tuberculosis in Dhaka Metropolitan City - Gulshan, Jahida; Farah, Subrina (Dhaka University Journal of Science, 2015)
This study aims to determine the age of first infection of pulmonary tuberculosis in Dhaka, the capital of Bangladesh. Registered cases at an arbitrarily selected chest disease clinic in Dhaka under the National Tuberculosis Control Program (NTP) of Bangladesh was considered for this study. From the study of the sample of 303 cases, it was revealed that women are more likely to be affected by Tuberculosis bacilli at earlier ages as compared to men in Dhaka. Mann Whitney Median test showed a significant difference between the median age of first infection of male and female (p-value < 0.001). In addition it is also observed that there is a significant difference (p-value<0.05) between the median age of first infection between people with in-house occupational activities and individuals with outgoing occupational activities where outgoing people are infected by Tuberculosis bacilli at later ages than in-house workers. An exponential regression model shows significant effect of the variables sex and place of occupational activities on the age of first infection (p-value < 0.05). DOI: http://dx.doi.org/10.3329/dujs.v62i1.21961 Dhaka Univ. J. Sci. 62(1): 49-53, 2014 (January)